Inheritance Distribution of Adopted Children in The Perspective of Customary Law and Islamic Law Compilation: Case Study of the Application of Inheritance Law in Kudus - Kasdi, Abdurrohman; Anwar, Khoiril (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2019)
This article aims to examine the position of adopted children, determine the position of adopted children's inheritance rights, as well as the application of the distribution of inheritance for adopted children in Customary Law and Compilation of Islamic Law in Kudus Regency. The method used is qualitative with a comparative approach. The results showed that the teachings of Islam did not deny the existence of adopted children as far as giving welfare and education to children. The position of adopted children in customary law is influenced by the family or family system. Their position from one region to another varies. In the case of the application of the distribution of inheritance for adopted children in adat law in Kudus District, several provisions of customary law state that the portion of adopted children is equated with the portion of biological children (if there is inheritance rights), or through the will of their adopted parents. While the application of Islamic Law Compilation in the distribution of inheritance in Kudus Regency also regulates wasiat wajibah, a will determined by law even though the person concerned does not inherit it.